2017
DOI: 10.1001/journalofethics.2017.19.3.msoc1-1703
|View full text |Cite
|
Sign up to set email alerts
|

From Particularities to Context: Refining Our Thinking on Illness Narratives

Abstract: This paper examines how illness narratives are used in medical education and their implications for clinicians' thinking and care of patients. Ideally, collecting and reading illness narratives can enhance clinicians' sensitivity and contextual thinking. And yet these narratives have become part of institutionalizing cultural competency requirements in ways that tend to favor standardization. Stereotyping and reductionistic thinking can result from these pedagogic approaches and obscure structural inequities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Analysing staff and parent/guardian interviews together allowed us to bring these narratives together, in the pursuit of common experience amongst these stakeholders, and to inform development of effective models of care [ 18 , 24 , 25 ]. This is of particular importance where the success and failure of integrated care interventions, including care coordination, have always been context dependent [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysing staff and parent/guardian interviews together allowed us to bring these narratives together, in the pursuit of common experience amongst these stakeholders, and to inform development of effective models of care [ 18 , 24 , 25 ]. This is of particular importance where the success and failure of integrated care interventions, including care coordination, have always been context dependent [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fundamentally, however, every narrative consists of a person that constructs the narrative, a person that the narrative refers to, and an illness that is being integrated into biographical details (Hydén, 1997). Several important scholars have argued that illness narratives are forms of meaning-making, that allow patients, families and clinicians to understand how an illness manifests itself in a person and to situate the totality of the illness experience in reference to the broader relational and structural contexts of patients (Frank, 1995;Kleinman, 1988;Le et al, 2017). The role of community is particularly relevant in the case of children who are positioned as inherently relational, relying on their social circles to navigate the world they live in and contributing to the social circles in which they live (James & Prout, 1997).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Listening to the stories of patients also brings with it a potential for cultural competency and cultural sensitivity training so as to better understand the ways in which culture might shape the illness experience. Narrative also allows for reflections on the importance of critical reflection for practitioners (Le et al, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Studies covered topics such as advocacy, racial justice, health equity, health promotion, trauma research, chronic diseases, and palliative care (Appleton, 2008;Banks, 2012;Cueva et al, 2015;Davidson & Falola, 2020;Delker et al, 2020;Drew et al, 2010;Elk et al, 2020;Le et al, 2017;Marsters & Meaghan, 2019;Roche et al, 2005;Wipfli et al, 2015). Additionally, storytelling as the primary modality was found in communicable disease research in public health and medical anthropology (Frank et al, 2015;Gilliam et al, 2012;Kleinman & Benson, 2006;Le et al, 2017;Mohammadhosseini et al, 2016;Willis et al, 2014). Finally, the literature showed that primarily public health researchers and medical anthropologists implemented storytelling in their studies, with a few identified in criminology and agriculture (Bove & Tryon, 2018).…”
Section: How Was Storytelling Specifically Used?mentioning
confidence: 99%